Remote operation of embedded controllers designed using IOPT Petri-nets - Pereira, Fernando (2016)
This paper presents a new communication architecture to enable the remote control, monitoring and debug of embedded-system controllers designed using IOPT Petri nets. IOPT Petri nets and the related tools (http://gres.uninova.pt) have been used as a rapid prototyping and development framework, including model-checking, simulation and automatic code generation tools. The new architecture adds remote operation capabilities to the controllers produced by the automatic code generators, enabling quasi-real-time remote debugging and monitoring using the IOPT simulator tool. Furthermore, it enables the creation of graphical user interfaces for remote operation and the development of distributed systems where a Petri net model running on a central system supervises the actions of multiple remote subsystems. © 2015 IEEE.